The application of NPK fertilizer boosts the nutrient uptake status and biomass production of Vernonia amygdalina - Dwi Susanto; RUDIANTO AMIRTA (Smujo International, 2020)
Abstract. Susanto D, Amirta R. 2020. The application of NPK fertilizer boosts the nutrient uptake status and biomass production of Vernonia amygdalina. Nusantara Bioscience 12: 114-119. Vernonia amygdalina Delile is a medicinal plant introduced in Indonesia. This study aims to determine the nutrients absorption status and growth of V. amygdalina plants planted with a spacing of 1x1 m. The study used a complete randomized block design with NPK compound fertilizer treatment with five doses of fertilizer namely 0 g (without fertilizer) as a control, 40 g, 80 g, 120 g, and 140 g, three blocks each group consisted of 10 plants so that in total there were 150 plants. The results showed that NPK fertilizer increased growth and the biomass of V. amygdalina. The best growth of V. amygdalina plant was achieved in plants applied with 160g per plant NPK fertilizer in which the average of stem diameter and plant height were 6.69 ± 0.930 cm and 611.67 ± 12.71 cm, while the estimated biomass yield was 407 tons.ha-1. The most nutritional elements accumulated in plant biomass was the calcium (1279.49 kg.ha-1), followed by magnesium (1167.0642 kg.ha-1), phosphorus (536.64 kg.ha-1), potassium (419.71 kg.ha-1) and nitrogen (134.4 kg.ha-1). We propose that these base nutrients are highly necessary for the cultivation of V. amygdalina as biomass feedstock or medicine plant.